Idiopathic intracranial hypertension in a patient with a history of migraine: a case report - Gonçalves, Christian; Kuhn, Leonardo José; De Lazari, Alan Henrique; De Lazari, Kassia Beatriz Valério Saibert; De Oliveira, Sara Pessoa; Barboza, Bárbara Evelin Gonçalves (Headache Medicine, 2024)
Idiopathic Intracranial Hypertension in a Patient with a History of Migraine: A Case Report GONÇALVES, Christian1; KUHN, Leonardo José1; DE LAZARI, Alan Henrique1; DE LAZARI, Kassia Beatriz Valério Saibert1; OLIVEIRA, Sara Pessoa de2; BARBOZA, Barbara Evelin Gonçalves3 1Academics of the Medicine Course at the Centro Universitário Integrado de Campo Mourão – PR 2 Physician, Neurologist, Master, Professor at the Centro Universitário Integrado de Campo Mourão - PR 3 Physician, Ophthalmologist, Professor at the Centro Universitário Integrado de Campo Mourão – PR Contact with author: GONÇALVES, Christian Email: cristiangoncalves08@hotmail.com Address: Av. Jorge Walter 1039, apt 02, Centro, Campo Mourão – PR – Brasil. Introduction: Idiopathic intracranial hypertension (IIH) is a condition whose cause is not well understood, characterized by increased pressure within the skull without evidence of brain mass or hydrocephalus. It mainly affects women of childbearing age and is associated with obesity. Objective: Emphasize the importance of early diagnosis of IIH and the use of appropriate treatments. Case Report: 44-year-old woman with a long history of migraines with visual aura since menarche, characterized by intense unilateral pulsatile headache, accompanied by photophobia, phonophobia, osmophobia and occasionally nausea with vomiting. In the last three months before the consultation, there was an increase in the frequency of attacks, with pain occurring three times a week. His personal history includes congenital Dumping syndrome, history of smoking (29 years/pack) and presbyopia, initial weight of 76kg. After an initial period of treatment with topiramate and nortriptyline, which was effective, the patient showed a significant reduction in seizures. However, in January 2022, she was referred by an ophthalmologist due to bilateral papilledema, presenting atypical neurological symptoms such as retrocular pain, amaurosis fugax and holocranial headache. The initially normal imaging tests led to a lumbar puncture, which revealed elevated CSF pressure (32.5 cm of water), diagnosing idiopathic intracranial hypertension (IIH). Treatment was started with acetazolamide, resulting in partial improvement of headache symptoms, but with side effects such as nausea and tingling. The patient presented with a recurrence of symptoms in March 2023, after a stressful period at work, requiring acute treatment with prednisone. Over time, with adjustments in therapy and frequent monitoring, there was complete regression of papillary edema and partial resolution of visual symptoms, and the visual field was not damaged. Current weight of 70kg. Conclusion: This case highlights the challenges in diagnosing and managing IIH in patients with a prior history of migraine, emphasizing the need for a multidisciplinary and adaptive approach. Effective management required body weight control and medication adjustments to control neurological and ophthalmological symptoms leading to complete regression of papillary edema and the visual field was undamaged. Keywords: Migraine with aura; Idiopathic intracranial hypertension; Papilledema.